The analysis of the efficiency of a master-slave parallel algorithm - Raimondas Čiegis; Ramūnas Šablinskas (Lietuvos Matematikos Rinkinys)
A general master-slave parallel algorithm is described. Three applications are investigated and results of numerical experiments with various clusters of workstations are given. PVM library is used in computations as a message passing interface.